Antioxidants level in serum of patients with high cholesterol - Ameera Hamdoon (College of Education for Pure Sciences, 2008)
Abstract This study included evaluation the relationship between cholesterol and antioxidants level in the human with hypercholesterolemia . Blood of 33 samples were collected from patients with hypercholesterolemia 18 male and 15 female with age ranging between (42 - 60 )year . 20 samples of blood were also collected from human with normal cholesterol (10 male , 10 female ) , this group considered the control group . Cholesterol , Vitamin C , Glutathione , SOD activity , peroxy nitrite ,and albumin levels , were measured in the serum of both groups . The statistical results showed a significant increase (p < 0.05) in the SOD activity and peroxy nitrite concentration in the human with hypercholesterolemia for both sex compared with the control group , while insignificant increase was showed in the albumin levels in the hypercholesterolemia patients compared with control group . The results also showed a significant decrease (p < 0.05 ) in vitamin C and glutathione levels in the patients with hypercholesterolemia for both sex compared with control group . This study demonstrated that there was a relationship between antioxidants levels and hypercholesterolemia patients , male and female include (Vitamin C , Glutathione , Peroxy nitrite , Superoxide Dismutas enzyme ).